Third Party Mediated Politeness in Salwa Bakr’s Short Story Zināt Fī Janāzat al-Ra'īs: A Brown and Levinson Analysis - Dhya' Qisthina; Masri'ah Masri'ah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
This study aims to analyze the representation of Brown and Levinson’s politeness strategies in third-party mediated speech in Salwa Bakr’s short story, Zināt Fī Janāzat al-Ra’īs. Employing a qualitative approach with a descriptive-analytical framework, the study analyzed the text using the extralinguistic correspondence method to associate linguistic components with the social context of the narrative. The analysis reveals that the mediator’s involvement manifests uniquely within each category of Brown and Levinson's strategies, altering the direct desires of the uneducated protagonist to navigate a strict social hierarchy. This linguistic alteration acts as a survival mechanism to protect the protagonist from state repression. The study ultimately concludes that in Bakr’s narrative, politeness toward authority emerges as a result of the scribe’s mediation rather than the speaker’s expression. This literary case study enhances sociopragmatic research by illustrating how class, literacy differences, and institutional obstacles influence politeness, providing a theoretical hypothesis for future empirical research in real-world professional, judicial, or community interpreting contexts.